Conservation Efforts of Asian Wild Water Buffalo - Kherwar, Pramod Kumar; Bhattarai, Ajaya (Journal of Buffalo Science, 2021)
Asian Wild Water Buffalo with the scientific name Bubalus bubalis arnee is recorded as an imperiled species in the International Union for Conservation of Nature (IUCN’s) Red List of Threatened Species wetland-subordinate. More number Wild Water Buffalo in Nepal are found at the Koshi Tappu Wildlife Reserve (KTWR), situated on the floodplain of the Koshi River in Province 1. This species is in danger because of a high anthropogenic pressing factor going from natural surroundings weakening to hybridization with homegrown Buffalo. Various preservation and work mediations have been attempted to shield the biodiversity, especially the wild buffalo populace in the KTWR. The people group-based supportable administration approach profiting both protection and work of neighborhood individuals is important to guarantee the drawn-out preservation of the species. But it is not happening, so the Government of Nepal translocated 18 Wild Water Buffaloes to Chitwan National Park, and the environment is not suitable for them. There is the possibility to translocate Wild Water Buffaloes in the Babai flood plain of Bardia National Park for conservation.